High energy and average power femtosecond laser for driving mid-infrared optical parametric amplifiers - Malevich, P. (2013)
We have developed the first (to our knowledge) femtosecond Tm-fiber-laser-pumped Ho:YAG room-temperature chirped pulse amplifier system delivering scalable multimillijoule, multikilohertz pulses with a bandwidth exceeding 12 nm and average power of 15 W. The recompressed 530 fs pulses are suitable for broadband white light generation in transparent solids, which makes the developed source ideal for both pumping and seeding optical parametric amplifiers operating in the mid-IR spectral range.